Dunkirk : the history behind the major motion picture - Levine, Joshua, 1970- (New York, NY : William Morrow, an imprint of HarperCollinsPublishers, 2017)
Recounts the Battle of Dunkirk and the daring evacuation of the British Army from the European continent, revealing the stories of the soldiers and civilians who made a difference that day.
Includes bibliographical references (pages 347-354).
Keywords: Dunkirk, Battle of, Dunkerque, France, 1940.; World War, 1939-1945 -- France; Dunkerque (France), Battle of, 1940.; World War, 1939-1945 -- France